PENDAMPINGAN PERENCANAAN KEUANGAN DAN PENGENDALIAN PRODUKSI PADA PERUSAHAAN MANUFAKTUR SAAT MASA PANDEMI COVID-19 PADA CV. PELUFI ENGINEERING DI BANTAR GEBANG BEKASI TIMUR - ATIKA RAHMI (Institut Bisnis Muhammadiyah Bekasi, 2021)
This study aims to assist CV. Pelufi Engineering, manufacturing business in good financial management. A business must be well managed. This research is descriptive. This research is descriptive in form using qualitative data. The data sources used are primary data from interviews and secondary data regarding the financial literature. The results of this study indicate that the understanding of CV. Pelufi Engineering is inadequate and still requires assistance. Strategies that have been applied in financial management properly in this study are separating personal money from business money. 2. Make the budget as best as possible 3. Avoid spending that has no impact on the business, 4. Good supply management. 5. Record business transactions 6. Control and supervise cash flow and provide a reserve fund for the smooth running of business capital